Potential of a sequence-based antigenic distance measure to indicate equine influenza vaccine strain efficacy - Daly, Janet M.; Elton, Debra (Elsevier, 2013)
The calculation of pepitope values, a sequence-based measure of antigenic distance between strains, was developed for human influenza. The potential to apply the pepitope value to equine influenza vaccine strain selection was assessed. There was a negative correlation between pepitope value and vaccine efficacy for pairs of vaccine and challenge strains used in cross-protection studies in ponies that just reached statistical significance (p = 0.046) only if one pair of viruses was excluded from the analysis. Thus the pepitope value has potential to provide additional data to consider in the decision-making process for updating equine influenza vaccine strains. However, further work is required to define the epitopes of the equine H3N8 haemagglutinin protein recognised by equine antibodies, which could lead to refinement of the pepitope value calculation. Furthermore, other factors such as vaccine potency and virulence of circulating strains may also influence vaccine efficacy.